Recent Progress of Quantum Dot‐Based Photonic Devices and Systems: A Comprehensive Review of Materials, Devices, and Applications. Issue 3 (18th December 2020) - Kim, Jaehyun; Song, Seungho; Kim, Yong-Hoon; Park, Sung Kyu
Abstract : Recently, photonic technologies have attracted lots of interests in the demand of high‐performance sensor devices. In particular, multifunctional photodetectors based on low‐dimensional nanomaterials have enabled to address complex environmental conditions and data processing for wide range of emerging applications, such as soft robotics, biomedical devices, and neuromorphic computing hardware, translating into mechanically flexible platforms that can offer reliable information. Semiconducting quantum dots (QDs) are one of the promising candidates for such photonic applications due to their excellent optical absorption coefficient, wide bandgap tunability, and structural stability as well as high‐throughput production capabilities, such as low‐cost, large‐area, and complementary metal–oxide–semiconductors (CMOS) compatible solution processability. Herein, essential investigations of the emerging photonic devices and systems are presented, focusing on materials, devices, and applications. In addition, diverse hybrid device architectures, which integrate the QD materials with various semiconductors, are fully examined to introduce the newly developed high‐performance wearable photodetectors and neuromorphic applications. Finally, research challenges and opportunities of the QD‐based photonic devices are also discussed, keeping forward‐looking perspective and system points of view. Abstract : Herein, essential investigations of quantum dots‐based emerging photonic devices and systems are presented. Particularly, the various designs and photonic device structures such as light‐emitting devices, photodiodes, photoconductors/phototransistors, solar cells, memory devices, and neuromorphic devices are discussed. Subsequently, image‐ and bio‐sensors, and their flexible/wearable applications as well as CMOS integration with QD devices and upconversion photodetectors are investigated.